Pengungkapan Sustainability Reporting Berbasis Digital Pada Lembaga Keuangan Syariah: Analisis Akuntansi Dan Tata Kelola Syariah - Andrianto Andrianto; Muh Nashiruddin Darajat; Juliana Zahra (Jurnal Kajian Ilmiah, 2026)
This study aims to analyze the implementation of digital-based sustainability reporting in Islamic financial institutions and identify the challenges and opportunities faced. The main problem in this study is the suboptimal integration between accounting systems, digital technology, and sharia governance in supporting comprehensive sustainability reporting. This study used a qualitative approach using in-depth interviews with informants consisting of financial managers, internal auditors, and the Sharia Supervisory Board. The results indicate that reporting practices are still in the early stages of digital transformation, with various obstacles such as limited measurement of non-financial information, low reporting standards, and the suboptimal role of sharia governance. Nevertheless, digitalization provides benefits in increasing transparency and access to information. This study also produces an integrative conceptual model that combines accounting, digital, and sharia dimensions as a framework for developing digital sustainability reporting. These findings are expected to form the basis for developing more effective and sustainable sustainability reporting policies and practices in Islamic financial institutions.